A Phylogenetically Informed Comparison of GH1 Hydrolases between Arabidopsis and Rice Response to Stressors - Cao, Yun-Ying; Yang, Jing-Fang; Liu, Tie-Yuan; Su, Zhen-Feng; Zhu, Fu-Yuan; Chen, Mo-Xian; Fan, Tao; Ye, Neng-Hui; Feng, Zhen; Wang, Ling-Juan; Hao, Ge-Fei; Zhang, Jianhua; et al. (Frontiers in Plant Science, 2017)
Glycoside hydrolases Family 1 (GH1) comprises enzymes that can hydrolyze β-O-glycosidic bond from a carbohydrate moiety. The plant GH1 hydrolases participate in a number of developmental processes and stress responses, including cell wall modification, plant hormone activation or deactivation and herbivore resistance. A large number of members has been observed in this family, suggesting their potential redundant functions in various biological processes. In this study, we have used 304 sequences of plant GH1 hydrolases to study the evolution of this gene family in plant lineage. Gene duplication was found to be a common phenomenon in this gene family. Although many members of GH1 hydrolases showed a high degree of similarity in Arabidopsis and rice, they showed substantial tissue specificity and differential responses to various stress treatments. This differential regulation implies each enzyme may play a distinct role in plants. Furthermore, some of salt-responsive Arabidopsis GH1 hydrolases were selected to test their genetic involvement in salt responses. The knockout mutants of AtBGLU1 and AtBGLU19 were observed to be less-sensitive during NaCl treatment in comparison to the wild type seedlings, indicating their participation in salt stress response. In summary, Arabidopsis and rice GH1 glycoside hydrolases showed distinct features in their evolutionary path, transcriptional regulation and genetic functions.